CO2 and CH4 emissions from streams in a lake‐rich landscape: Patterns, controls, and regional significance. Issue 3 (10th March 2014) - Crawford, John T.; Lottig, Noah R.; Stanley, Emily H.; Walker, John F.; Hanson, Paul C.; Finlay, Jacques C.; Striegl, Robert G.
Abstract Aquatic ecosystems are important components of landscape carbon budgets. In lake‐rich landscapes, both lakes and streams may be important sources of carbon gases (CO2 and CH4) to the atmosphere, but the processes that control gas concentrations and emissions in these interconnected landscapes have not been adequately addressed. We use multiple data sets that vary in their spatial and temporal extent during 2001–2012 to investigate the carbon gas source strength of streams in a lake‐rich landscape and to determine the contribution of lakes, metabolism, and groundwater to stream CO2 and CH4. We show that streams emit roughly the same mass of CO2 (23.4 Gg C yr−1; 0.49 mol CO2 m−2 d−1) as lakes at a regional scale (27 Gg C yr−1) and that stream CH4 emissions (189 Mg C yr−1; 8.46 mmol CH4 m−2 d−1) are an important component of the regional greenhouse gas balance. Gas transfer velocity variability (range = 0.34 to 13.5 m d−1) contributed to the variability of gas flux in this landscape. Groundwater inputs and in‐stream metabolism control stream gas supersaturation at the landscape scale, while carbon cycling in lakes and deep groundwaters does not control downstream gas emissions. Our results indicate the need to consider connectivity of all aquatic ecosystems (lakes, streams, wetlands, and groundwater) in lake‐rich landscapes and their connections with the terrestrial environment in order to understand the full nature of the carbon cycle.